IMPLEMENTASI KURIKULUM MERDEKA MADRASAH IBTIDAIYAH (MI) (Studi Analisis Kebijakan KMA RI No. 347 Tahun 2022) - Anas Anas; Akhmad Zaenul Ibad; Nova Khairul Anam; Fitri Hariwahyuni (Pusat Riset dan Inovasi Nasional, 2023)
The Independent Curriculum was determined by the Ministry of Education and Culture and the Minister of Religion of the Republic of Indonesia has issued a decree number 347 of 2022 regarding guidelines for implementing the Independent Curriculum in madrasah. So the implementation of the Independent Curriculum at Madrasah Ibtidaiyah becomes a demand for madrasah. The research uses a library research. The data research related to the Independent Curriculum and the Decree of the Minister of Religion of the Republic of Indonesia number 347 of 2022 concerning the Independent Curriculum. The Analyzing data of this research using a way to describe the data in the study (content analysis). The Independent Madrasah Ibtidaiyah curriculum implements learning according to the abilities of students which gives more space to develop student’s basic character and competence. The Character abilities that support interactive learning is by developing abilities and having characters in the form of noble character, diversity, independence, critical and creative reasoning. Have a focus on essential learning and adapts to the abilities of the students. The Independent Curriculum at Madrasah Ibtidaiyah was developed in Indonesia with the aim to improve the quality of education. Its implementation is adjusted to the needs and characteristics of students which can facilitate the learning process without feeling burdened in the implementation of learning in Madrasahs. It is because the process of implementing the Independent Madrasah Ibtidaiyah Curriculum is more profound, fun and independent. Implementation of the Independent Madrasah Ibrtidaiyah Curriculum in accordance with KMA RI No. 347 Year 2022 is supported by the existence of the Independent Learning platform which is easily accessible. The Independent Curriculum application contains teaching tools needed by students and teachers to facilitate the learning process.